PENGEMBANGAN E-MODUL SISTEM PENDINGIN MESIN UNTUK SISWA XI TKR SMK MUHAMMADIYAH GAMPING - Fuad Anwar Sudibyo; Samsul Hadi; Ardi Widyatmoko (JURNAL VOKASI DEWANTARA (JVD), 2021)
This study aims to determine the feasibility of a good and quality engine cooling system E-module. This research development model has four steps, including the preliminary study step, the development step, the field test step and the deployment step. The e-Module teaching materials were evaluated from two material experts and two media experts then tested on 16 XI TKR students of SMK Muhammadiyah Gamping. The collection of respondents used is a questionnaire / questionnaire Likert scale model of four coverage options. the acquisition of material expert score of 3.36 is included in the "very good" category, the acquisition of data from media experts of 3.26 is classified in the "feasible" category, the acquisition of field tests of 3.41 is classified as "very good" The number of respondents obtained by material experts, media experts, and field testing obtained an average score of 3.35 from the acquisition of a maximum score of 4 so that it was included in the category of "very feasible / very good"Keywords: Floating E-Module, Learning Media, Machine Cooling SystemAbstrak: Penelitian bertujuan mengetahui kelayakan E-modul sistem pendingin mesin yang baik dan berkualitas. Model penelitian pengembangan ini terdapat empat langkah, diantaranya langkah studi pendahuluan, langkah pengembangan, langah tahap uji lapangan dan langkah penyebaran. Bahan ajar e-Modul dievaluasi dari dua ahli materi dan dua ahli media selanjutnya diujicobakan pada 16 siswa XI TKR SMK Muhammadiyah Gamping. Pengumpulan responden yang di pakai adalah kuesioner/angket skala Likert model empat cakupan pilihan. perolehan nilai ahli materi sebesar 3,36 termasuk dari kategori â€œsangat layakâ€, perolehan data ahli media sebesar 3,26 tergolong pada kategori â€œlayakâ€, perolehan uji lapangan sebanyak 3,41 tergolong pada kategori â€œsangat baikâ€, jadi rata-rata jumlah dari perolehan responden oleh ahli materi, ahli media,dan uji lapangan memdapatkan rata-rata skor sebanyak 3,35 dari perolehan skor maksimal 4 sehingga masuk kategori dari Â â€œsangat layak/sangat baikâ€Kata Kunci : Pengembangan E-modul, Media Pembelajaran, Sistem Pendingin Mesin